Interactive english games [ (Lesson For Life, 2008)
Minimum system requirements: Intel Pentium/Celeron/AMD/Similar 667 MHz or faster, Windows Vista/XP/ME/2000/98, 128MB RAM, 1024x768 resolution, 2xDVD-ROM drive, 16-bit Windows compatible sound card, 100MB free hard disk space